IMPLEMENTATION OF MORAL EDUCATION AGAINST SOCIAL DEVIATION - Agus Leo Handoko; Wulandari; Indah Suciati; Hajerina; Ary Analisa Rahma (Adisam Publisher, 2024)
This article describes the implementation of moral education against social deviations. Moral education is an important thing in the development of a person's or individual's character in order to avoid disgraceful behavior which becomes social deviation by violating norms in society. Moral education plays a very important role and is very important to implement both in the family school and at school as well as the role of parents and teachers. and community leaders in an effort to teach good character. Moral education against social deviance is aimed at protecting someone from bad deeds or bad actions that are not in accordance with existing norms in education, society, nation and state. So the high and low level of a person's moral judgment determines whether or not moral behavior or actions are good in society. Instilling moral education is very important because it can be seen the impact of social deviations, namely psychological trauma, fear, insecurity, resentment, decreased enthusiasm for learning, concentration, creativity, loss of initiative, students' (mental) endurance and others.